Influence of dance therapy on the functional mobility of children with spastic hemiparetic cerebral palsy - D.C. Garção (Desafio Singular, 2011)
The aim of this study was to investigate the influence of dance therapy on the functional mobility of children with spastic hemiparetic cerebral palsy. Ten female children (mean age 7.2 ± 1.2 years) diagnosed with cerebral palsy were included. In order to evaluate their functional mobility, standing (D) and walking, running and jumping (E) dimensions from GMFM were applied, and measurements were carried out in two phases: 1) control, six weeks without any motor intervention, and 2) activity, 18 sessions of dancing. Children were assessed three times: first, before the control phase, second, after the control phase, and third, at the end of the dancing phase. Kruskal-Wallis (p < .05) and Dunn tests (p < .05) were used. There were no changes in performance between the two first phases of evaluation (p = 1.00), however, at the end of the dancing phase a significant increase was measured in relation to D (p < .01) and E dimensions (p < .01). Results showed that dance therapy influences children's functional mobility.